1995
DOI: 10.2136/sh1995.4.0121
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of Two Sandy Spodosol Hydrosequences in Michigan

Abstract: This study was conducted to determine the effect of natural drainage on sand‐, silt‐, and clay‐size minerals in two sandy hydrosequences of Spodosols in northern Michigan. Depth to water tables were monitored using piezometers. Minerals in the dominant sand fraction were identified and quantified using a petrographic microscope. Minerals in the silt and clay fractions were identified and semiquantified using x‐ray diffraction. Sand mineralogy was dominated by quartz with small amounts of feldspars and sericite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
1
0
2
Order By: Relevance
“…Saturation appeared to aid in the formation of smectite, since the Btg horizon of Pedon P2 was saturated longer than any other B horizon. Haile-mariam and Mokma (1995) found that transformation of vermiculite to smectite in E horizons of Spodosols was hindered by saturation.…”
Section: Clay Mineralogymentioning
confidence: 99%
“…Saturation appeared to aid in the formation of smectite, since the Btg horizon of Pedon P2 was saturated longer than any other B horizon. Haile-mariam and Mokma (1995) found that transformation of vermiculite to smectite in E horizons of Spodosols was hindered by saturation.…”
Section: Clay Mineralogymentioning
confidence: 99%
“…Estudando a assembléia mineralógica de Espodossolos com diferentes níveis de hidromorfia, Haile-Mariam & Mokma (1995), encontraram, na fração silte, principalmente quartzo e em menor proporção feldspato. Na fração argila, as hidrosseqüências estudadas indicam que ocorreu a transformação de muscovita em vermiculita nos horizontes B e de vermiculita em esmectita nos horizontes E, onde é o mineral dominante nesta fração.…”
Section: Introductionunclassified
“…Estudando a assembléia mineralógica de Espodossolos com diferentes níveis de hidromorfia, Haile-Mariam & Mokma (1995) encontraram, na fração silte, principalmente quartzo e, em menor proporção, feldspato. Na fração argila, as hidrosseqüências estudadas indicam que ocorreu a transformação de muscovita em vermiculita nos horizontes B e de vermiculita em esmectita nos horizontes E, em cuja fração a esmectita é o mineral dominante.…”
Section: Introductionunclassified